Prosecutorial immunity: a review of Rosli Bin Dahlan v Tan Sri Abdul Gani Bin Patail & Ors - Ali Mohamed, Ashgar Ali (LexisNexis, 2015)
Article 145(3) of the Federal Constitution and s 376(1) of the Criminal Procedure Code conferred on the attorney general, the public prosecutor, the power, exercisable at his discretion, to institute, conduct or discontinue any proceedings for any offence. The prosecutorial discretion includes the decision on whether to commence prosecution against a suspect, and if so, the possible charges against him, whether to discontinue criminal proceeding, and whether to appeal against the acquittal of the accused or against the sentences passed by the court. The discretion vested in the attorney general above is unfettered and it is not open to the court to interfere or question the discretion. In relation to the above, this article considers the issue of whether a civil suit lies against the attorney general or his deputies for malicious prosecution or misfeasance in public office when the attorney general or his deputies had engaged in prosecutorial misconduct or abuse of prosecutorial power. For example, where the public prosecutor had knowingly manufactured the evidence, coerced witnesses into giving false testimony, where the charge was politically motivated or by other improper motives. In other words, whether the prosecutorial immunity enjoyed by the public prosecutor is an absolute or qualified immunity. The discussion is based on the recent High Court decision in Rosli bin Dahlan v Tan Sri Abdul Gani bin Patail & Ors. It is an undisputed fact that if the public prosecutor can be subjected to lawsuits for the decision he makes, he may become reluctant to file charges except in the most obvious cases. Apart from the above, it could also raise fear that it could bring a wave of frivolous filings that may clog up the court system.